Development and Validation of Stability-Indicating RP-UPLC Method for Simultaneous Determination of Related Substances of S(−)Amlodipine and S(−)Metoprolol Succinate in Fixed Dose Combination Tablet Dosage Form. (20th October 2014) - Shitole, Suresh; Gurjar, Mukund; Shah, Mahesh; Pimple, Srikant; Bal, Gobardhan; Patel, Rahul
Abstract : A novel, rapid, accurate, sensitive, precise, and stability-indicating reverse-phase ultra-performance liquid chromatographic (RP-UPLC) method was developed and validated for determination of related substances of S(−)Amlodipine and S(−)Metoprolol Succinate in fixed dose combination tablet dosage form. The chromatographic separation was achieved with the use of Acquity UPLC HSS T3, 1.8  μ m, 2.1 × 100 mm analytical column at 45°C employing a gradient elution. Mobile phase consisting of mobile phase-A (solution containing 5.0 gm of sodium dihydrogen phosphate monohydrate per liter of water and Acetonitrile in the ratio of 95 : 5) and mobile phase-B (Acetonitrile) was used at a flow rate of 0.5 mL min −1 with injection volume of 10  μ L and the detection was done at 232 nm using UV detector. The retention times of S(−)Metoprolol Succinate and S(−)Amlodipine were found to be 2.8 minutes and 8.1 minutes, respectively. During method validation all the parameters were evaluated as per ICH guidelines, which remained well within acceptable limits. This method can be used for the estimation of related substances of S(−)Amlodipine and S(−)Metoprolol Succinate in fixed dose combination tablet dosage form.